MENGUJI KONSISTENSI BADAN PEMERIKSAAN KEUANGAN (BPK) DALAM TRANSPARANSI INFORMASI PUBLIK : STUDI ATAS LAPORAN HASIL PEMERIKSAAN KEUANGAN (LHPK) - Steffi Zafia Furqan (Supremasi Hukum: Jurnal Penelitian Hukum, 2026)
This study aims to analyze the implementation of the BPK audit function on the Audit Result Report (LHP) from the perspective of Law Number 14 of 2008 concerning Public Information Disclosure (UU KIP). The main problem studied is the extent to which the public can access the BPK audit results as part of the implementation of the principles of transparency and accountability in a democratic government system. The method used is normative juridical research with a statutory, conceptual, and comparative approach. The legal materials analyzed include Law Number 15 of 2004, Law Number 15 of 2006, and the 2008 KIP Law, supported by legal literature and decisions of the Central Information Commission (KIP). The results of the study indicate that normatively, the BPK LHP is open public information as long as it does not contain state secrets or material related to legal processes. However, in practice, the implementation of information disclosure within the BPK environment remains limited due to overlapping norms between the principles of openness and the protection of state secrets. Several KIP decisions, such as Number 009/VII/KIP-PS/2014 and Number 076/VII/KIP-PS/2018 emphasize the need for clarity in BPK's internal regulations in conducting consequence tests on public information. This study concludes that public information disclosure at BPK is not yet fully optimal and requires strengthening internal regulations and institutional commitment to balance the public's right to information with the protection of strategic state data. Thus, the implementation of information disclosure by BPK is expected to strengthen public trust and support the creation of transparent, accountable governance in accordance with the principles of good governance.